An Information System for Management of National Open University of Nigeria (NOUN) Study Centres - Ikpe, Peter Adoga; Adamu, Idama (West African Journal of Open and Flexible Learning, 2013)
An information system that will help keep track of course materials distribution, counselling history, students and staff records, and financial operations, all in respect of the course materials at the Study Centres of the National Open University of Nigeria (NOUN) is discussed. This integrated system will help facilitate the duties of the clerks, administrative officers, accountants, store officers, ICT staff, centre director, library officers, counsellors and students with a unique interface created for each user. The nature of demand for course materials by students was determined using records of monthly demand for five-course materials selected at random, for a period of six years. The reordering pattern of the Yola Study Centre was studied using information on stock supplied between 2005 and 2010. An information system based on the Periodic Review Inventory Model was developed to provide better inventory management in the study centres.